Adaptation or resilience strategies of entrepreneurs in the context of the COVID-19 pandemic: Study of three cases in Peru, Chile and Spain - Cerón Valencia, Fernando Paul (2024)
This article presents a study of the situations of three entrepreneurs from Peru, Chile and Spain in the COVID-19 pandemic framework. An attempt has been made to understand their responses and the components of their particular resilience, as well as the endogenous and exogenous resources with which they faced their states of personal and organizational uncertainty. It also addresses the frameworks of contextual crises –of different natures– in which companies had to be managed by analyzing the structural and conjunctural capacities to respond from their managerial commands.